Max Bense/Aloísio Magalhães (Germany, 1969): the transcultural and popular context of Der Weg eines Zeichens (ARS, 2018)
If the Modernist impulse requires new approaches, then many argue that highlighting the networks of artistic exchange is one way of reactualizing the Modernist paradigm. In 1969, Brazilian artist and designer Aloísio Magalhães (1927-1982) exhibited a series of photographs at the study gallery at Studium Generale, University of Stuttgart, an exhibition space for interdisciplinary discourse founded by Max Bense (1910*1990) in 1958. In this study I want to discuss key aspects of this exhibition project, comparing it with the Brazilian concretist movement and Lina Bo Bardi’s exhibitionary visions, as well as to examine the different cultural approaches to Magalhães photographic project and its common grounds with formalism, concretism and sign theory.